Peran Akal dalam Al-Qur’an dengan Pendekatan Rasional dan Filosofis dalam Kitab Mafatih Al-Ghaib - Yasrul Ihza Saputra; Nurusshobah (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
Imam Fakhruddin al-Razi's Tafsir Mafatih al-Ghaib is an important work in the tafsir tradition that integrates rational and philosophical approaches in interpreting the verses of the Qur'an. As an expert in theology, philosophy, and logic, al-Razi used highly rational and critical methods in interpreting the meaning of the Qur'an, focusing not only on linguistic and legal aspects, but also from a theological and metaphysical point of view. In this commentary, al-Razi combines logic, philosophy, and scientific knowledge to provide a deeper understanding of complex and metaphysical verses. The approach includes in-depth textual analysis as well as considering the historical context and philosophical dimensions of revelation, resulting in a broader meaning. Apart from that, al-Razi also developed an interpretation of the mutasyabihat verses using a metaphorical approach that makes it easier for the human mind to understand. This research uses a qualitative descriptive analysis method to explore the application of al-Razi's rational and philosophical approach in Mafatih al-Ghaib and assess its impact on theological and philosophical understanding in Islam. The research results show that although al-Razi's interpretation has faced criticism regarding the combination of reason and revelation which is considered to reduce the spiritual dimension, this work is still appreciated because of its contribution to enriching the understanding of the Qur'an. Al-Razi succeeded in connecting revelation with reason and science, producing rational and reflective interpretations. Therefore, al-Razi's tafsir in Mafatih al-Ghaib is considered one of the important works that provides a comprehensive understanding of sacred texts in the Islamic tafsir tradition